Analysis of clinical features and arylsulfatase B gene mutation in thirteen Chinese children with mucopolysaccharidosis type VI - Zheng, Jipeng (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2014)
OBJECTIVE: Mucopolysaccharidosis type VI (MPS VI) or Maroteaux-Lamy syndrome is an autosomal recessive lysosomal storage disease caused by a deficiency of arylsulfatase B(ARSB), which is required in the degradation of dermatan sulfate and chondroitin sulfate. The deficiency of ARSB leads to an accumulation of dermatan sulfate and chondroitin sulfate in lysosomes and gross excretion in the urine.Few articles about clinical study and ARSB gene mutation analysis of Chinese MPS VI patients were published. This study aimed to explore the clinical features and characteristics of ARSB gene in Chinese children with MPS VI